OPTIMALISASI PERSONAL BRANDING SISWA MELALUI PEMBUATAN WEBSITE CV DI ERA DIGITAL - Dimas Aqil Setyawan; Julio Rohmatulloh Hardiansyah; Marisa Firdha; Muhammad Gifary Nezar; Pinhan Fatoni; Ratu Ayu Fatimah; Razky Zaihan Daulay; Robi Ramadhan; Salsabilla Pixy Anjelita; Siti Halimatul Aliyah; Muhammad Azis Sularso (Abdi Jurnal Publikasi, 2026)
The rapid development of digital technology requires students to possess adaptive skills, particularly in building effective personal branding. Personal branding plays an important role in enhancing students’ competitiveness in both academic and professional environments. This report discusses the optimization of students’ personal branding through the development of a Curriculum Vitae (CV) website as a professional, informative, and easily accessible digital medium. The methods used include observation, design, and implementation of a CV website by utilizing simple web technologies tailored to students’ needs. The results indicate that the CV website helps students present their personal identity, competencies, experiences, and portfolios in a structured and attractive manner. Furthermore, the use of a CV website increases students’ self-confidence and readiness to face further education opportunities and job selection processes. Therefore, the development of a CV website can be considered an effective solution for optimizing students’ personal branding in the digital era.